2017
DOI: 10.1002/hep.28786
|View full text |Cite
|
Sign up to set email alerts
|

An ectopically expressed serum miRNA signature is prognostic, diagnostic, and biologically related to liver allograft rejection

Abstract: The ability to noninvasively diagnose acute cellular rejection (ACR) with high specificity and sensitivity would significantly advance personalized liver transplant recipient care and management of immunosuppression. We performed microRNA (miRNA) profiling in 318 serum samples from 69 liver transplant recipients enrolled in the Immune Tolerance Network immunosuppression withdrawal (ITN030ST) and Clinical Trials in Organ Transplantation (CTOT-03) studies. We quantified serum miRNA at clinically indicated and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 23 publications
3
68
0
Order By: Relevance
“…miRNAs are involved in the regulation of gene expression through RNA silencing and post-transcriptional gene silencing via binding to the 3'-untranslated region (3'-UTR) of specific mRNAs (11,12). miRNAs regulate diverse aspects of development and physiology, such as metabolic diseases (13), cardiovascular disease (14,15), immune dysfunction (16,17) and cancer (18,19). A large number of studies have reported that miRNAs are key factors in regulating cell differentiation and growth, migration, apoptosis and necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are involved in the regulation of gene expression through RNA silencing and post-transcriptional gene silencing via binding to the 3'-untranslated region (3'-UTR) of specific mRNAs (11,12). miRNAs regulate diverse aspects of development and physiology, such as metabolic diseases (13), cardiovascular disease (14,15), immune dysfunction (16,17) and cancer (18,19). A large number of studies have reported that miRNAs are key factors in regulating cell differentiation and growth, migration, apoptosis and necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…In the search for viable biomarkers, microRNAs (miRNAs) have gained interest due to their low complexity, stability, and organ specificity. Many studies have shown that miRNAs released in biofluids like serum, urine, and bile can be used as sensitive and accurate biomarkers . They are associated with a variety of pathologic conditions and control many cellular processes including tissue injury and repair .…”
mentioning
confidence: 99%
“…miRs can withstand harsh environmental conditions, and because the perfusate circulates through the entire liver during machine perfusion, miR levels in perfusate provide a better and non‐invasive representation of the entire liver compared to miR levels measured in total RNA samples from biopsies . Furthermore, miRs have been shown to be earlier and more sensitive markers of liver damage than more conventional markers such as AST or ALT, and machine perfusion potentially allows for an even more representative and dynamic evaluation of the liver graft . In addition, machine perfusion can be used for the resuscitation of grafts but fast and predictive biomarkers, such as miRs, are necessary to assess the effects of the treatment provided .…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, miRs have been shown to be earlier and more sensitive markers of liver damage than more conventional markers such as AST or ALT, and machine perfusion potentially allows for an even more representative and dynamic evaluation of the liver graft. 16,25,26 In addition, machine perfusion can be used for the resuscitation of grafts but fast and predictive biomarkers, such as miRs, are necessary to assess the effects of the treatment provided. [27][28][29][30] Especially HDmiR-122, which is involved in several processes in the liver such as lipid metabolism, has the po- Studies have shown that HDmiR-122 levels in graft preservation fluid are higher in DCD grafts and in livers that went on to develop EAD and NAS.…”
Section: Discussionmentioning
confidence: 99%